A Study On The Relationship Of Rock Strenght And Grindability Of Limestone, Granite And Metallic Ore - Ahmad Romil, Rozaida (Universiti Sains Malaysia, 2018)
The grindability of rock samples depends on both the mechanical properties of the materials being ground and the mechanism of grinding. Rock strength is one of the mechanical properties of rock, and it is defined as the maximum value of stress at which the rock fails. This study has been carried out with the aim to study the effect of rock strength on the Bond work index of different rock sample. Point load test was carried out to determine the point load strength index and to estimate the uniaxial compressive strength of the rock sample. While, Bond ball mill grindability test was performed to determine the Bond grindability work index of the rock sample. The relationship between rock strength and grindability of different rock sample was determined based on the correlation of compressive strength and Bond grindability work index. There is a strong correlation found between the compressive strength of tested rock and the Bond work index according to the equation Wi = 36.95ln(x) – 62.31 and Wi = 36.95ln(x) – 179.76 with the correlation coefficient 92%. From this study, it is found that there are a strong relationship between rock strength and grindability of limestone, granite and metallic ore.